2018
DOI: 10.1021/acsomega.8b00913
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Omp2a-Based Supported Lipid Bilayers: Comparison with Polymeric Bioinspired Membranes

Abstract: Omp2a β-barrel outer membrane protein has been reconstituted into supported lipid bilayers (SLBs) to compare the nanomechanical properties (elastic modulus, adhesion forces, and deformation) and functionality of the resulting bioinspired system with those of Omp2a-based polymeric nanomembranes (NMs). Protein reconstitution into lipid bilayers has been performed using different strategies, the most successful one consisting of a detergent-mediated process into preformed liposomes. The elastic modulus obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 73 publications
(143 reference statements)
1
9
0
Order By: Relevance
“…Similarly, the resistance reported for Omp2a protein supported onto lipid bilayers, which exhibited much less mechanical strength than 3layered films, was of 3.7 kΩ•cm 2 . 19 These results confirm that npPLA/PEDOT/npPLA/VDAC films behave as smart biomimetic membranes fulfilling the self-standing and mechanical integrity requirements of many applications in different areas of the biomedical field, such as nanofluidics, biosensing and energy conversion.…”
Section: Characterization Of the Immobilized Vdac36 Proteinsupporting
confidence: 72%
See 1 more Smart Citation
“…Similarly, the resistance reported for Omp2a protein supported onto lipid bilayers, which exhibited much less mechanical strength than 3layered films, was of 3.7 kΩ•cm 2 . 19 These results confirm that npPLA/PEDOT/npPLA/VDAC films behave as smart biomimetic membranes fulfilling the self-standing and mechanical integrity requirements of many applications in different areas of the biomedical field, such as nanofluidics, biosensing and energy conversion.…”
Section: Characterization Of the Immobilized Vdac36 Proteinsupporting
confidence: 72%
“…EIS assays evidenced that, with respect to nanoperforated PLA (npPLA) nanofilms without protein, those loaded with the protein showed enhanced conductivity and selectivity against some ions. 19 In a recent study, we reported a new approach for preparing free-standing films that combines the mechanical strength and flexibility of processed npPLA nanosheets with the electrochemical response of anodically polymerized CPs. 20 More specifically, 5layered membranes made of three npPLA layers separated by two anodically polymerized poly(3,4-ethylenedioxythiophene) (PEDOT) layers were prepared and used as Faradaic motors able to push a huge amount of mass.…”
Section: Introductionmentioning
confidence: 99%
“…Though PC lipids are not found in bacterial membranes, they are often included in model membrane studies, because of the difficulties using formulations with POPE and POPG alone. A POPC/POPE/POPG (4:3:1) mixture prepared by evaporating the solvent and rehydrating the lipid thin film on an ITO surface results in a membrane with a resistance of 4.2 kΩ cm 2 . In this work, we are able to remove the irrelevant POPC component and demonstrate the formation of the POPE/POPG lipid bilayer by using the SA method on PEDOT:PSS.…”
Section: Resultsmentioning
confidence: 97%
“…Despite the capacity of npPLA and npPLA/Omp2a NMs to be free-standing, the difficulties associated with their handling limited ion diffusion and electrical measurements, which were conducted using NMs supported onto ITO substrates [12]. Under these conditions, the conductivity of npPLA/Omp2a membranes was comparable to that of the same protein supported onto lipid bilayers (LB/Omp2a) [13]. However, the suppression of the solid support to have biomimetic and flexible platforms with conducting channels for the metabolite transport is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantages of previous studies based on PNMPy/Omp2a, npPLA/Omp2a and LB/Omp2a [11][12][13], the novelty of the present work relies on the design of an advanced functional platform by immobilizing porin proteins onto a smart free-standing biomimetic membrane. This biomimetic membrane consists of three PLA layers with submicrometric perforations (pPLA layers) separated by two layers of a CP, which was prepared by electropolymerization.…”
Section: Introductionmentioning
confidence: 99%